Case Report: Ocular Myasthenia Gravis - Pace, Rodger (Canadian Journal of Optometry, 1983)
Myasthenia gravis is a chronic disease producing muscle weakness. Ocular muscle involvement occurs in a large percentage of myasthenic patients. A case of myasthenia gravis with initial symptoms of diplopia and extraocular muscle involvement is presented. The ocular signs of myasthenia gravis and diagnostic procedures are emphasized.